2022
DOI: 10.1249/mss.0000000000002848
|View full text |Cite
|
Sign up to set email alerts
|

Acute Citrulline Blunts Aortic Systolic Pressure during Exercise and Sympathoactivation in Hypertensive Postmenopausal Women

Abstract: PurposeHypertensive postmenopausal women (PMW) have exaggerated exercise systolic blood pressure (SBP) due to impaired functional sympatholysis. l-Citrulline (CIT) supplementation attenuates aortic SBP responses to cold pressor test (CPT)–induced vasoconstriction in young men. We hypothesized that acute CIT ingestion would attenuate aortic SBP and leg hemodynamic responses during exercise and CPT (EX + CPT).MethodsFifteen hypertensive PMW (61 ± 7 yr) were randomly assigned to consume either 6 g of CIT or place… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Conversely, acute ingestion of 10 g of L-CIT, the maximal clinically effective dose, did not improve microvascular reactive hyperemic blood flow in healthy older men [ 53 ] and older adults with heart failure [ 54 ]. Moreover, we found that an acute 6 g dose of L-CIT was unable to improve superficial femoral artery blood flow or vascular conductance during low-intensity exercise [ 55 ]. These previous findings suggest that L-CIT may need to be supplemented for at least 4 weeks to observe significant benefits in endothelial function.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, acute ingestion of 10 g of L-CIT, the maximal clinically effective dose, did not improve microvascular reactive hyperemic blood flow in healthy older men [ 53 ] and older adults with heart failure [ 54 ]. Moreover, we found that an acute 6 g dose of L-CIT was unable to improve superficial femoral artery blood flow or vascular conductance during low-intensity exercise [ 55 ]. These previous findings suggest that L-CIT may need to be supplemented for at least 4 weeks to observe significant benefits in endothelial function.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, CIT did not reduce wave reflection during PEMI without cold exposure, indicating that CIT is less efficient to attenuate haemodynamic responses to mild sympathetic-mediated vasoconstriction in healthy young men (23) . Thus, CIT may be more efficacious in populations with exaggerated BP and sympathetic responses to exercise and cold exposure, such as hypertensive postmenopausal women and older adults (17,22) . The efficiency of CIT to attenuate Pf and Pb responses to cold-induced sympathetic vasoconstriction was previously demonstrated after 2 weeks of supplementation in older adults (22) .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, evidence indicates that CIT can reduce aortic SBP, PP, and pressure wave amplitude responses to sympathetic overactivation induced via cold exposure in older adults (22) . Similarly, acute L-citrulline (6 g) and chronic CIT (6 g/d) attenuated aortic SBP responses to exercise and to PEMI combined with cold exposure in hypertensive postmenopausal women (17) and healthy young men (23) , demonstrating the ability of CIT to effectively control BP responses to conditions with excessive sympathetic activity. However, a single dose of CIT had no BP lowering effect during dynamic exercise without cold exposure in postmenopausal women (17) , suggesting that a higher dose may be necessary to reduce exercise BP.…”
mentioning
confidence: 92%
See 1 more Smart Citation